DEVELOPMENT OF EQUIPMENT FOR GRINDING ORGANIC FILLERS FOR BIODEGRADABLE POLYMERS - KRAVETS, OLEKSANDR; TITOVA, OLENA; KRAVETS, VASYL; KABAT, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This work is dedicated to the development of methods and equipment for grinding organic fillers, which play a crucial role in the production of biodegradable polymers. Organic fillers help reduce material costs and improve properties such as biodegradability, mechanical characteristics, and compostability. The fine grinding process of organic fillers is a critical stage in the production of composite materials based on biodegradable polymers, which are widely used in the food, construction, agricultural, and biomedical industries, among others. The use of fillers in biodegradable polymers allows for the creation of environmentally friendly materials with a wide range of properties that meet modern sustainability requirements.This study presents the conceptual design of an experimental setup and the development of a grinding mill for processing organic fillers. The vertical shaft impact mill is designed for continuous fine and ultra-fine grinding of organic fillers. It enables material drying without additional heat supply. The mill combines high-speed impact fragmentation, particle attrition in vortex flows, and air classification of the material at each stage.The research investigates the geometric parameters of the mill, the elements of boundary separation, and their relationship with the technological parameters of grinding. The study examines how the width of the mill's separation rings affects the particle size distribution of the ground material. During the experimental studies, the following plant raw materials were processed: coniferous wood and wheat straw. Grinding was carried out with an air supply through the mill in the range of 400–600 m³/h. The mill temperature under different settings ranged from 52°C to 67°C. The particle size distribution of the product was analyzed using sieve analysis and digital optical microscopy.
Keywords: organic fillers; vertical shaft impact mill; biodegradable polymers